Center volume and outcomes in pediatric heart transplantation—Bigger is better until it isn't. Issue 12 (13th August 2018) - Scheel, Janet; Canter, Charles E.
Abstract : The relationship of center volume to outcomes in pediatric heart transplantation is more complex than anticipated. See Singh and Gauvreau's article onpage 2914 .